Women Image In Algerian Cinema Between The Past And The Present - بوالعام بلال; جنيح أمين (University of Eloued جامعة الوادي, 2024)
Abstract: the article deal with the aesthetics of cinema as an art that studies reality and embodies ideas with a human dimension in an attractive artistic way that conveys societal suffering and fragility. Women are considered a philosophical subject like art and beauty, presented cinematically as part of reality and as a model of social truth. A playful dancer, a night girl, a drug dealer, or a naive rural girl, a servant, and in the least opportunities as a university student or as an employee, she is a cinematic booty on the sidelines of events, and it has portrayed her outwardly in a few opportunities as an actor and a driver of events, or a positive one standing behind and beside the man, Sometimes young and adolescence and sometimes Mature, elderly, and sometimes either single, divorced, or widowed, and rarely portrayed as a wife, mother, or university student. The woman staying at home is presented as emotional, highly sensitive, and even the struggling ones remained neglected, consumed, deviant, unproductive, non-participant in development, absent from the fields of production, and unable to creativity. As for the worker, her image is devoid of feelings of motherhood and femininity, estranged from customs and traditions, or is the subject of sex in all films.
Keywords: Algerian women; Women image; Algerian cinema